ALISHER NAVOI-GREAT POET, THE IMPACT OF HIS EDUCATIONAL WORKS FOR THE YOUNGER GENERATION - Inoyatova G.N. (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract: This article deals with the study of the efficient and diverse creative heritage of Hazrat Alisher Navoi, a great poet and scientist, a famous logical thinker, the founder of Uzbek literature and language. Navoi’s heritage encompass philosophy, political science, literary critism, scientific and lyrical works.